IMPLEMENTATION OF ONLINE LEARNING AND ITS IMPACT ON LEARNING ACHIEVEMENTS OF MATHEMATICS EDUCATION STUDENTS - Simon M. Panjaitan; Agusmanto J. B. Hutauruk; Christina Sitepu; Sanggam P. Gultom; Parlindungan Sitorus; Melati Riani Marbun; Cahyana Hotmauli Sinaga (Jurnal Infinity, 2023)
Implementing online learning in a higher education environment requires an analysis of learning outcomes and their impact on students, lecturers, and the institutions that administer the learning. The implementation of online learning shows that the learning process takes place and the readiness of lecturers and students to implement online learning. The impact given by online learning is in the form of GPA and student perceptions of the learning process they experience. Based on the research results, various findings were obtained, including that mastery of online learning LMS was not optimal, learning outcomes in the form of GPA were relatively high, students' perceptions of online learning were still low, especially in terms of lecturer readiness and students' confidence in their competence after participating in learning.